Studi kasus penggunaan indikator kinerja di berbagai organisasi pelayanan kesehatan pemerintah = A case study on the use of performance indicator in various government's health service organizations - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Background: This study was based on the fact that the performance of government health service organizations t HSOs) arc relatively hard to evaluate in absence of complete and clear performance indicators. Consequently. an accountable measurement of performance is difficult to undertake. This study aimed to study the currently used perkwmance indicators at various HSOs. Method: This study was a case study research. The subjects were 8 FISOs representing various types of HSOs from bureaucratic to corporate organizations. The respondents were directors of the organizations. The locations of the study were 5 HSOs in Bantu!, 2 HSOs in Yogyakarta, and l in Magelang. The currently used performance indicators were compared to several indicators developed based on knir aspects of Balanced score Card (BSC). Results: The results showed that the bureaucratic organization had no clear and complete performance indicators as the result of inadequate strategic planning so that their visions. missions. and objectives were unclear. The bureaucratic organization had not yet prepared for developing and applying The BSC indicators. Meanwhile the corporate health service organizations had clear and complete performance indicators, and were relatively ready to develop and apply the performance indicator based on BSC. Conclusion: In order to have sound performance accountability indicators, attempts to plan kw clear and complete performance indicators are needed to improve the quality of care, to satisfy the community needs.